Financing Channels and Monetary Policy in a Dual Banking System: Evidence from Islamic Banks in Indonesia. (14th December 2016) - Zulkhibri, Muhamed; Sukmana, Raditya
Abstract : Using Indonesian Islamic banking data from 2003 to 2014, this article employs a panel regression methodology to investigate the responses of Islamic banks to changes in financing rates and monetary policy, which may differ depending on their characteristics. The results suggest that the financing rate has a negative impact on financing at Islamic banks, while bank‐specific characteristics have a positive influence on it. The size and amount of capital have a greater impact than liquidity on financing at Islamic banks. However, changes in monetary policy are insignificant on bank financing, which implies that the transmission of monetary policy through the Islamic segment of the banking sector is weak. Furthermore, the weak impact of monetary policy on bank financing can be explained by the dramatic expansion of Islamic banks during the sample period, which contributed to a substantial increase in deposit growth and a high liquidity position.